2019
DOI: 10.1158/1078-0432.ccr-19-1025
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Class, First-in-Human Study Evaluating LV305, a Dendritic-Cell Tropic Lentiviral Vector, in Sarcoma and Other Solid Tumors Expressing NY-ESO-1

Abstract: Purpose: LV305 is a modified, third-generation, nonreplicating, integration-deficient lentivirus-based vector designed to selectively transduce dendritic cells in vivo. LV305 induces expression of the New York Esophageal Squamous Cell Carcinoma-1 (NY-ESO-1) cancer testis antigen in dendritic cells, promoting immune responses against NY-ESO-1–expressing tumors. This phase I study evaluated the safety, immunogenicity, and preliminary efficacy of LV305 in patients with sarcoma or other solid tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 24 publications
2
53
0
1
Order By: Relevance
“…In ESCC, mature LAMP3 + DCs has been reportedly associated with increasing tumor‐infiltrating CD8 + T cells 58 . Recently, promising findings of a phase I study on LV305, an engineered harmless virus targeting DCs, have been released 59 . LV305 upregulated the expression level of the New York ESCC‐1 (NY‐ESO‐1) cancer testis antigen in DCs, promoting immune responses against NY‐ESO‐1‐expressing tumors 60 .…”
Section: Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ESCC, mature LAMP3 + DCs has been reportedly associated with increasing tumor‐infiltrating CD8 + T cells 58 . Recently, promising findings of a phase I study on LV305, an engineered harmless virus targeting DCs, have been released 59 . LV305 upregulated the expression level of the New York ESCC‐1 (NY‐ESO‐1) cancer testis antigen in DCs, promoting immune responses against NY‐ESO‐1‐expressing tumors 60 .…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…All treatment‐related AEs were grade 1 or 2. The disease control rate was 56% in all patients 59 . Further investigation of LV305 is continuously explored, possibly in combination with a boosting vaccine and/or other agents, such as immune checkpoint inhibitors.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…The above-mentioned lentiviral vectors have been tested in cancer patients with different solid NY-ESO-1-expressing tumors [45]. In this phase I clinical trial, so-called LV305 was assessed (Table S1 (Supplementary Materials)), which represents the so-called ZVex, a third generation lentiviral-based Sindbis virus glycoprotein functionalized vector, which is replication-incompetent and integration-deficient to reduce lentiviral-related side effects [94].…”
Section: Dc-sign Receptor Targetingmentioning
confidence: 99%
“…Following the success of preclinical studies, recent phase 1 vaccination trial evaluating LV305 in NY-ESO-1 expressing solid tumors also showed promising results. LV305, was found to selectively induce NY-ESO-1 specific expression in dendritic cells and promoting tumor responses in patients [87]. Similarly, phase 1 study in synovial and myxoid round cell liposarcoma with CMB305 vaccine containing LV305 was shown to prime NY-ESO-1 specific T cell responses leading to enhanced overall survival [88].…”
Section: Current Pre-clinical and Clinical Trials Of Ny-eso-1 Antigenmentioning
confidence: 98%